Overview of the Monopoly Rights of the Social Security Administering Body (BPJS) from the Perspective of Citizens' Health Protection - Rulan Pobi; Nur Mohamad Kasim; Fence M Wantu (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
The monopoly right to health protection granted to the Social Security Administration Agency (BPJS) in Law no. 24 of 2011 concerning BPJS is an attempt to organize a health insurance program effectively and efficiently. However, this monopoly right also raises several problems, first, institutional problems in the implementation of the national social security system (SJSN) and related to choosing a hospital location that is not in accordance with the wishes of BPJS participants. In this legal research, it has a normative research type with a statutory approach related to the BPJS monopoly right in health protection. The research results show that in order to ensure that the national health insurance program can run effectively, coordinated and integrated efforts are needed between the government, BPJS Health, health service providers, and the community. The government needs to increase the allocation of the health budget, ensure efficient use of funds, and find alternative sources of funding